A low-density thermal conductive potting glue and its preparation method and application

By applying vinyl MQ silicone resin coating modification on thermally conductive flame retardant filler, the problems of low thermal conductivity, high density and poor flame retardant properties of silicone potting for batteries in new energy vehicles are solved, and higher thermal conductivity and flame retardant properties are achieved, and the tensile strength and elasticity of the potting glue are improved.

CN119242263BActive Publication Date: 2025-04-15GUANGZHOU XINYUE NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411265743.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-15
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing silicone potting glue for batteries in new energy vehicles has low thermal conductivity, high density, poor flame retardant properties, and high viscosity are not conducive to potting. It has insufficient earthquake resistance after curing, poor weather resistance, small applicable temperature range, and is prone to aging and cracking.

Method used

The thermally conductive flame retardant filler is coated and modified by low-density vinyl MQ silicone, which improves the dispersion and bonding force of the filler in silicone rubber, reduces the density of the potting glue, and improves tensile strength and elasticity through a clustered crosslinking structure.

Benefits of technology

With less addition of thermally conductive flame retardant filler, better thermal and flame retardant performance can be achieved, the density of potting glue is reduced, tensile strength and elasticity can be improved, and earthquake resistance and weather resistance can be enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005037078610000031
    Figure BDA0005037078610000031
  • Figure BDA0005037078610000032
    Figure BDA0005037078610000032
  • Figure BDA0005037078610000061
    Figure BDA0005037078610000061
Patent Text Reader

Abstract

The present invention belongs to the technical field of silicone rubber, and discloses a low-density thermally conductive potting glue, a preparation method thereof and an application thereof. The low-density thermally conductive potting glue comprises component A and component B; component A comprises the following components by weight: 80 to 100 parts of side vinyl silicone oil and / or end vinyl silicone oil; 100 to 150 parts of vinyl MQ silicone resin coated modified thermally conductive flame retardant filler; 0.005 to 0.02 parts of catalyst; component B comprises the following components by weight: 80 to 100 parts of side vinyl silicone oil and / or end vinyl silicone oil; 100 to 150 parts of vinyl MQ silicone resin coated modified thermally conductive flame retardant filler; 10 to 30 parts of end hydrogen silicone oil; 0.05 to 0.2 parts of inhibitor; 0 to 0.2 parts of color powder. The present invention adopts low-density MQ silicone resin to coat and modify the filler, which can achieve good thermal conductivity and mechanical properties while reducing the amount of filler added, and significantly reduce the density of the potting glue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicone rubber, and in particular relates to a low-density thermally conductive potting adhesive and a preparation method and application thereof. Background Art

[0002] Thermally conductive potting glue is mainly used for potting of new energy vehicle batteries to achieve waterproof, moisture-proof, dust-proof, insulation, thermal conductivity, confidentiality, corrosion resistance, temperature resistance, and shock resistance. At present, the commercially available silicone potting glue for new energy vehicle batteries has low thermal conductivity, high specific gravity, poor flame retardant performance, and high viscosity, which is not conducive to potting. After curing, the seismic strength is insufficient, the weather resistance is poor, the applicable temperature range is small, and it is easy to age and crack.

[0003] Existing organic silicone potting glue is mainly obtained by crosslinking vinyl silicone oil and hydrogen-containing silicone oil through a silylation reaction. For example, in our previous patent CN 116463104 A, a low-density thermally conductive potting glue is disclosed, which uses the reaction product of end-vinyl silicone oil and side hydrogen silicone oil, end-hydrogen silicone oil and end-side hydrogen-containing silicone oil as the base silicone rubber component. However, the reaction product of end-vinyl silicone oil and side hydrogen silicone oil, end-hydrogen silicone oil and end-side hydrogen-containing silicone oil is mainly a linear or comb-type crosslinked product. In order to improve its tensile strength, it is necessary to increase its molecular weight and crosslinking strength, but the linear or comb-type crosslinked product molecules are closely arranged, and the elasticity decreases after increasing its molecular weight and crosslinking strength. This phenomenon is particularly obvious after adding thermal conductive fillers and reinforcing fillers, resulting in insufficient seismic performance of the cured product.

[0004] At present, the method to improve the thermal conductivity of thermally conductive potting glue is mainly to add high-content thermally conductive fillers, and the commonly used thermally conductive fillers mainly include aluminum oxide, aluminum nitride, silicon carbide, zinc oxide, titanium dioxide, boron nitride, etc. However, the density of the above thermally conductive fillers is much larger than that of silicone rubber, which leads to a higher density of the potting glue; in addition, the above thermally conductive fillers have poor dispersion performance in silicone rubber and weak bonding with silicone rubber. In order to improve the thermal conductivity, the content of the thermally conductive fillers needs to be increased, which will lead to a decrease in the tensile strength and elasticity of the potting glue, so it is difficult to achieve satisfactory comprehensive performance.

[0005] Patent CN 104861661 A discloses using one or more of low-density fillers such as hollow glass microspheres, hollow phenolic microspheres, and plastic microspheres to reduce the density of the potting compound, and using one or more of reinforcing fillers such as fumed silica, precipitated silica, calcium carbonate, and quartz powder to increase the strength. However, it still does not solve the problems of potting compound elasticity and seismic resistance, nor does it solve the problems of poor dispersibility and weak bonding of high-proportion thermal conductive fillers. Summary of the invention

[0006] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a low-density thermal conductive potting glue. The present invention uses low-density vinyl MQ silicone resin to coat and modify the thermal conductive flame retardant filler, which can achieve good thermal conductive flame retardant performance while reducing the amount of thermal conductive flame retardant filler added, and reduce the density of the potting glue; at the same time, the dispersibility of the thermal conductive flame retardant filler in the silicone rubber matrix is ​​enhanced and the bonding force with the silicone rubber matrix is ​​improved, thereby improving the mechanical properties of the potting glue.

[0007] Another object of the present invention is to provide a method for preparing the low-density thermally conductive potting adhesive.

[0008] Another object of the present invention is to provide an application of the low-density thermally conductive potting adhesive in the potting of new energy vehicle batteries.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A low-density thermally conductive potting adhesive, comprising component A and component B;

[0011] The A component includes the following components by weight:

[0012] 80-100 parts of side vinyl silicone oil and / or terminal vinyl silicone oil; 100-150 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 0.005-0.02 parts of catalyst;

[0013] The B component includes the following components by weight:

[0014] 80-100 parts of side vinyl silicone oil and / or end vinyl silicone oil; 100-150 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 10-30 parts of end hydrogen silicone oil; 0.05-0.2 parts of inhibitor; 0-0.2 parts of color powder;

[0015] The vinyl MQ silicone resin coated modified thermally conductive flame retardant filler is prepared by the following method:

[0016] (1) adding a thermally conductive filler and a flame retardant filler to an ethanol aqueous solution and stirring and dispersing them uniformly, then adding ammonia water to adjust the pH value to 8-10, adding tetraethyl orthosilicate dropwise and stirring to react, and after the reaction is completed, filtering and drying the solid phase, and crushing to obtain a silica-coated modified thermally conductive flame retardant filler;

[0017] (2) adding the silica-coated modified thermally conductive flame-retardant filler into the vinyl MQ silicone resin solution and stirring to disperse the mixture evenly; spraying and granulating the resulting slurry to obtain the vinyl MQ silicone resin-coated modified thermally conductive flame-retardant filler.

[0018] Preferably, the viscosity of the side vinyl silicone oil or the terminal vinyl silicone oil is 100 to 5000 mPa·s (25° C.), and the vinyl content (mass percentage calculated as -CH2=CH2) is 2% to 10%.

[0019] The typical molecular structure of the side vinyl silicone oil or the end vinyl silicone oil is as follows:

[0020]

[0021] In the formula, Me represents a methyl group, and Vi represents a vinyl group.

[0022] Pendant vinyl silicone oil or terminal vinyl silicone oil are both commonly used silicone oil raw materials in the field.

[0023] Preferably, the catalyst is any one of chloroplatinic acid, chloroplatinic acid-isopropanol, and Custer's catalyst (1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex).

[0024] Preferably, the hydrogen-terminated silicone oil is a hydrogen-terminated silicone oil with a hydrogen content (mass percentage of terminal hydrogen) of 0.02% to 1.5%; more preferably, a hydrogen-terminated silicone oil with a hydrogen content of 0.05% to 1%; most preferably, a combination of a hydrogen-terminated silicone oil with a hydrogen content of 0.05% to 0.2% and a hydrogen-terminated silicone oil with a hydrogen content of 0.4% to 1%. The typical molecular structure of the hydrogen-terminated silicone oil is shown below:

[0025]

[0026] Preferably, the inhibitor is one or more of 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 2-phenyl-3-butynyl-2-ol and vinyl ring.

[0027] Preferably, the thermally conductive filler in step (1) is one or more of aluminum oxide, aluminum nitride, silicon carbide, zinc oxide, titanium dioxide, and boron nitride.

[0028] Preferably, the flame retardant filler in step (1) is one or more of aluminum hydroxide, magnesium hydroxide, decabromodiphenyl ether, melamine, antimony oxide, and zinc borate.

[0029] Preferably, the mass ratio of the thermal conductive filler, the flame retardant filler and tetraethyl orthosilicate added in step (1) is 100:15-30:15-30.

[0030] Preferably, the vinyl MQ silicone resin solution in step (2) refers to a toluene solution, a xylene solution or a cyclopentasiloxane solution of a vinyl MQ silicone resin having a molecular weight of 2000 to 6000 g / mol.

[0031] Preferably, the mass ratio of the silica-coated modified thermally conductive flame-retardant filler to the vinyl MQ silicone resin contained in the vinyl MQ silicone resin solution in step (2) is 100:10-30.

[0032] The method for preparing the low-density thermally conductive potting adhesive comprises the following steps:

[0033] 1) Weighing each component by weight, adding side vinyl silicone oil and / or end vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, and catalyst into a vacuum reactor and stirring and mixing to obtain component A;

[0034] 2) Weigh each component by weight, add side vinyl silicone oil and / or end vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, end hydrogen silicone oil, and color powder into a vacuum reactor and stir to mix, then add an inhibitor and stir to mix to obtain component B.

[0035] The application of the above-mentioned low-density thermal conductive potting glue in the potting of new energy vehicle batteries.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention adopts a specific vinyl MQ silicone resin to coat the modified thermally conductive flame retardant filler to replace the conventional thermally conductive flame retardant filler. On the one hand, the coating of the vinyl MQ silicone resin can significantly improve the dispersibility and bonding strength of the thermally conductive flame retardant filler in silicone oil and silicone rubber, and can achieve better thermal conductivity and flame retardant effects with a smaller amount of thermally conductive flame retardant filler added. Due to the reduced amount of thermally conductive flame retardant filler added and the low density of the MQ silicone resin, the density of the resulting potting compound can be significantly reduced; on the other hand, the surface-coated vinyl MQ silicone resin can participate in the cross-linking reaction of the silicone rubber, so that the modified thermally conductive flame retardant filler can form a chemical bond with the silicone rubber matrix, significantly improving the reinforcement effect and ultimately improving the tensile strength of the potting compound; on the other hand, due to its structural characteristics, the active vinyl groups of the vinyl MQ silicone resin are almost all distributed in the outer layer, and it has many reaction sites and high reaction activity. Through the subsequent reaction with the hydrogen-terminated silicone oil, a clustered cross-linked structure can be formed in the side vinyl silicone oil and / or the side vinyl silicone oil molecules. Compared with the conventional comb-type cross-linked product, the clustered cross-linked structure can maintain the good flexibility and elasticity of the resulting potting compound.

[0038] (2) In the preparation process of the vinyl MQ silicone resin coated modified thermally conductive flame retardant filler of the present invention, silica is first used for coating modification, which can improve the subsequent bonding strength between the vinyl MQ silicone resin and the vinyl MQ silicone resin, so that it can form a chemical bond with the uncapped Q segment of the vinyl MQ silicone resin, thereby improving the coating stability of the vinyl MQ silicone resin and ultimately improving the dispersion stability and bonding strength of the thermally conductive flame retardant filler in silicone oil and silicone rubber.

[0039] (3) The present invention further adopts a combination of terminal hydrogen silicone oils with different hydrogen contents (molecular weights) as a crosslinking agent for side vinyl silicone oil and / or end-side vinyl silicone oil, which can form crosslinking networks of different sizes in the side vinyl silicone oil and / or end-side vinyl silicone oil molecules, and further combines with the clustered crosslinking structure formed by the modified thermally conductive flame-retardant filler coated with vinyl MQ silicone resin, which can simultaneously achieve good mechanical strength and elasticity. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0041] Example 1

[0042] A low-density thermally conductive potting adhesive, comprising component A and component B;

[0043] The A component includes the following components by weight:

[0044] 90 parts of side vinyl silicone oil with a viscosity of 650 mPa·s (25° C.) and a vinyl content of 5.2%; 120 parts of vinyl MQ silicone resin-coated modified thermal conductive flame retardant filler; and 0.01 parts of Custer catalyst.

[0045] The B component includes the following components by weight:

[0046] 90 parts of side vinyl silicone oil with a viscosity of 650 mPa·s (25°C) and a vinyl content of 5.2%; 120 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 20 parts of terminal hydrogen silicone oil with a hydrogen content of 0.25%; 0.1 parts of inhibitor 3,5-dimethyl-1-hexyn-3-ol; and 0.1 parts of color powder.

[0047] The vinyl MQ silicone resin coated modified thermally conductive flame retardant filler is prepared by the following method:

[0048] (1) By weight, 100 parts of thermal conductive filler aluminum nitride and 20 parts of flame retardant filler aluminum hydroxide are added to an ethanol aqueous solution and stirred and dispersed uniformly, and then ammonia water is added to adjust the pH value to 9.5. Under room temperature, 20 parts of tetraethyl orthosilicate are added dropwise and stirred for reaction. The tetraethyl orthosilicate is added dropwise for 1.5 hours. After the addition is completed, the stirring reaction is continued for 0.5 hours. After the reaction is completed, the solid phase is filtered, dried, and crushed to obtain a silica-coated modified thermal conductive flame retardant filler.

[0049] (2) 100 parts of silica-coated modified thermally conductive flame-retardant filler are added to 100 parts of a 20% mass concentration of vinyl MQ silicone resin (molecular weight 4210 g / mol) toluene solution and stirred to disperse evenly. The resulting slurry is spray granulated to obtain a vinyl MQ silicone resin-coated modified thermally conductive flame-retardant filler.

[0050] The low-density thermally conductive potting glue is prepared by the following method:

[0051] 1) Weighing each component by weight, adding side vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, and catalyst into a vacuum reactor and stirring and mixing to obtain component A with a viscosity of 2320 mPa·s;

[0052] 2) Weigh each component by weight, add the side vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, terminal hydrogen silicone oil, and color powder into a vacuum reactor and stir and mix well, then add the inhibitor and stir and mix well to obtain component B with a viscosity of 2750 mPa·s.

[0053] The low-density thermally conductive potting glue obtained in this embodiment has a viscosity of 2540 mPa·s after mixing at a weight ratio of 1:1; and a specific gravity of 1.46 g / mL.

[0054] The low-density thermally conductive potting adhesive obtained in this embodiment has a hardness (Shore A) of 54 after being cured at 80° C. / 30 min; a tensile strength of 1.20 MPa; an elongation of 95.6%; and a thermal conductivity of 1.08 W / m·K.

[0055] Embodiments 2 to 12

[0056] The low-density thermally conductive potting adhesives of Examples 2 to 12 are different in composition from Example 1 according to the different terminal hydrogenated silicone oils listed in Table 1, and the rest are the same.

[0057] Table 1

[0058]

[0059]

[0060] The hardness, tensile strength, elongation and thermal conductivity of the obtained low-density thermal conductive potting glue were tested respectively, and the results are shown in Table 2 below.

[0061] Table 2

[0062] Example hardness Tensile Strength Elongation Thermal conductivity Example 1 54 1.20Mpa 95.6% 1.08W / m·K Example 2 42 0.62Mpa 131.5% 0.92W / m·K Example 3 48 0.78Mpa 116.4% 1.00W / m·K Example 4 51 1.06Mpa 105.2% 1.03W / m·K Example 5 57 1.28Mpa 90.7% 1.09W / m·K Example 6 63 1.31Mpa 87.4% 1.08W / m·K Example 7 67 1.38Mpa 70.9% 1.06W / m·K Example 8 72 1.42Mpa 52.0% 1.05W / m·K Example 9 56 1.30Mpa 98.2% 1.08W / m·K Example 10 62 1.35Mpa 108.1% 1.09W / m·K Embodiment 11 59 1.27Mpa 100.6% 1.07W / m·K Example 12 61 1.15Mpa 85.3% 1.05W / m·K

[0063] It can be seen from the results of Examples 1 to 8 in Table 2 that with the increase of the hydrogen content of the terminal hydrogen silicone oil, the hardness and tensile strength of the obtained thermal conductive potting glue show an increasing trend, but the elongation shows a decreasing trend. The reason is that the higher the hydrogen content of the terminal hydrogen silicone oil, the smaller the molecular weight and the greater the crosslinking density; with the increase of the crosslinking density, the strength increases and the elasticity decreases. The hydrogen content of the terminal hydrogen silicone oil can achieve good comprehensive performance when it is in the range of 0.05% to 1%. In addition, it can be seen from the results of Examples 9 to 11 that the combination of terminal hydrogen silicone oils with different hydrogen contents can achieve good strength and elongation at the same time compared with a single terminal hydrogen silicone oil, indicating that the effect of combined use is better. It can be seen from the results of Example 12 that the difference in hydrogen content of the terminal hydrogen silicone oil is too large to achieve a good combination effect. The combination of terminal hydrogen silicone oil with a hydrogen content of 0.05% to 0.2% and terminal hydrogen silicone oil with a hydrogen content of 0.4% to 1% can achieve good strength and elongation at the same time.

[0064] Example 13

[0065] A low-density thermally conductive potting adhesive, comprising a component A and a component B;

[0066] The A component includes the following components by weight:

[0067] 100 parts of side vinyl silicone oil with a viscosity of 960 mPa·s (25° C.) and a vinyl content of 4.5%; 100 parts of vinyl MQ silicone resin-coated modified thermal conductive flame retardant filler; and 0.02 parts of Custer catalyst.

[0068] The B component includes the following components by weight:

[0069] 100 parts of side vinyl silicone oil with a viscosity of 960 mPa·s (25°C) and a vinyl content of 4.5%; 100 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 15 parts of terminal hydrogen silicone oil with a hydrogen content of 0.08% and 15 parts of terminal hydrogen silicone oil with a hydrogen content of 0.8%; 0.06 parts of inhibitor 3,5-dimethyl-1-hexyn-3-ol; 0.1 parts of color powder.

[0070] The vinyl MQ silicone resin coated modified thermally conductive flame retardant filler is prepared by the following method:

[0071] (1) By weight, 100 parts of thermal conductive filler aluminum oxide and 15 parts of flame retardant filler aluminum hydroxide are added to an ethanol aqueous solution and stirred to disperse evenly, then ammonia water is added to adjust the pH value to 9, and 15 parts of tetraethyl orthosilicate are added dropwise at room temperature to react by stirring. The tetraethyl orthosilicate is added dropwise for 1.5 hours. After the addition is completed, the stirring reaction is continued for 0.5 hours. After the reaction is completed, the solid phase is filtered, dried, and crushed to obtain a silica-coated modified thermal conductive flame retardant filler.

[0072] (2) 100 parts of silica-coated modified thermally conductive flame-retardant filler are added to 100 parts of a 10% mass concentration of vinyl MQ silicone resin (molecular weight 5520 g / mol) toluene solution and stirred to disperse evenly. The resulting slurry is spray granulated to obtain a vinyl MQ silicone resin-coated modified thermally conductive flame-retardant filler.

[0073] The low-density thermally conductive potting glue is prepared by the following method:

[0074] 1) Weighing each component by weight, adding side vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, and catalyst into a vacuum reactor and stirring and mixing to obtain component A with a viscosity of 2460 mPa·s;

[0075] 2) Weigh each component by weight, add side vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, terminal hydrogen silicone oil, and color powder into a vacuum reactor and stir and mix, then add an inhibitor and stir and mix to obtain component B with a viscosity of 2850 mPa·s.

[0076] The low-density thermally conductive potting glue obtained in this embodiment has a viscosity of 2700 mPa·s after mixing at a weight ratio of 1:1; and a specific gravity of 1.42 g / mL.

[0077] The low-density thermally conductive potting adhesive obtained in this embodiment has a hardness (Shore A) of 53 after being cured at 80° C. / 30 min; a tensile strength of 1.29 MPa; an elongation of 113.4%; and a thermal conductivity of 1.05 W / m·K.

[0078] Embodiment 14

[0079] A low-density thermally conductive potting adhesive, comprising component A and component B;

[0080] The A component includes the following components by weight:

[0081] 80 parts of end-side vinyl silicone oil with a viscosity of 350 mPa·s (25° C.) and a vinyl content of 7.2%; 150 parts of vinyl MQ silicone resin-coated modified thermal conductive flame retardant filler; and 0.005 parts of Custer catalyst.

[0082] The B component includes the following components by weight:

[0083] 80 parts of end-side vinyl silicone oil with a viscosity of 350 mPa·s (25°C) and a vinyl content of 7.2%; 150 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 5 parts of end-hydrogen silicone oil with a hydrogen content of 0.08%, 5 parts of end-hydrogen silicone oil with a hydrogen content of 0.8%; 0.05 parts of inhibitor 3,5-dimethyl-1-hexyn-3-ol; 0.1 parts of color powder.

[0084] The vinyl MQ silicone resin coated modified thermally conductive flame retardant filler is prepared by the following method:

[0085] (1) By weight, 100 parts of thermal conductive filler aluminum nitride and 30 parts of flame retardant filler aluminum hydroxide are added to an ethanol aqueous solution and stirred to disperse evenly, then ammonia water is added to adjust the pH value to 10, and 30 parts of tetraethyl orthosilicate are added dropwise at room temperature to react by stirring. The tetraethyl orthosilicate is added dropwise for 1.5 hours. After the addition is completed, the stirring reaction is continued for 0.5 hours. After the reaction is completed, the solid phase is filtered, dried, and crushed to obtain a silica-coated modified thermal conductive flame retardant filler.

[0086] (2) 100 parts of silica-coated modified thermally conductive flame-retardant filler are added to 100 parts of a 30% mass concentration of vinyl MQ silicone resin (molecular weight 3680 g / mol) toluene solution and stirred to disperse evenly. The resulting slurry is spray granulated to obtain a vinyl MQ silicone resin-coated modified thermally conductive flame-retardant filler.

[0087] The low-density thermally conductive potting glue is prepared by the following method:

[0088] 1) Weighing each component by weight, adding side vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, and catalyst into a vacuum reactor and stirring and mixing to obtain component A with a viscosity of 2190 mPa·s;

[0089] 2) Weigh each component by weight, add the side vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, terminal hydrogen silicone oil, and color powder into a vacuum reactor and stir and mix, then add the inhibitor and stir and mix to obtain component B with a viscosity of 2310 mPa·s.

[0090] The low-density thermally conductive potting glue obtained in this embodiment has a viscosity of 2260 mPa·s after mixing at a weight ratio of 1:1; and a specific gravity of 1.52 g / mL.

[0091] The low-density thermally conductive potting adhesive obtained in this embodiment has a hardness (Shore A) of 46 after being cured at 80° C. / 30 min; a tensile strength of 1.21 MPa; an elongation of 93.7%; and a thermal conductivity of 1.10 W / m·K.

[0092] Comparative Example 1

[0093] A low-density thermally conductive potting adhesive, using unmodified thermally conductive filler and flame retardant filler, including component A and component B;

[0094] The A component includes the following components by weight:

[0095] 90 parts of side vinyl silicone oil with a viscosity of 650 mPa·s (25° C.) and a vinyl content of 5.2%; 100 parts of aluminum nitride as a thermal conductive filler; 20 parts of aluminum hydroxide as a flame retardant filler; and 0.01 parts of a Custer catalyst.

[0096] The B component includes the following components by weight:

[0097] 90 parts of side vinyl silicone oil with a viscosity of 650 mPa·s (25°C) and a vinyl content of 5.2%; 100 parts of aluminum nitride as a thermal conductive filler; 20 parts of aluminum hydroxide as a flame retardant filler; 20 parts of terminal hydrogen silicone oil with a hydrogen content of 0.25%; 0.1 parts of inhibitor 3,5-dimethyl-1-hexyn-3-ol; and 0.1 parts of color powder.

[0098] The low-density thermally conductive potting glue is prepared by the following method:

[0099] 1) Weigh each component by weight, add side vinyl silicone oil, thermal conductive filler aluminum nitride, flame retardant filler aluminum hydroxide, and catalyst into a vacuum reactor and stir to mix well to obtain component A with a viscosity of 2180 mPa·s;

[0100] 2) Weigh each component by weight, add vinyl silicone oil, thermal conductive filler aluminum nitride, flame retardant filler aluminum hydroxide, terminal hydrogen silicone oil, and color powder into a vacuum reactor and stir to mix, then add an inhibitor and stir to mix to obtain component B with a viscosity of 2460 mPa·s.

[0101] The low-density thermally conductive potting glue obtained in this comparative example has a viscosity of 2330 mPa·s after mixing at a weight ratio of 1:1; and a specific gravity of 1.58 g / mL.

[0102] The low-density thermally conductive potting adhesive obtained in this comparative example has a hardness (Shore A) of 65 after being cured at 80° C. / 30 min; a tensile strength of 0.97 MPa; an elongation of 73.5%; and a thermal conductivity of 0.94 W / m·K.

[0103] It can be seen from the comparison results of this comparative example and Example 1 that, under the condition of equal thermally conductive flame-retardant filler addition, the thermally conductive flame-retardant filler coated and modified by the vinyl MQ silicone resin of the present invention can significantly reduce the density of the obtained potting compound, because the density of the silica coating layer and the MQ silicone resin coating layer are significantly less than that of the unmodified thermally conductive filler. The thermally conductive flame-retardant filler coated and modified by the vinyl MQ silicone resin of the present invention can significantly reduce the hardness of the obtained potting compound and significantly improve the tensile strength, elongation and thermal conductivity. The reduction in hardness may be due to the fact that the clustered cross-linked structure formed can reduce the cohesive force of the cross-linked molecules compared to the comb-type cross-linked structure, and the MQ silicone resin coating modification has a significant improvement effect on the hardness increase and elasticity reduction caused by the thermally conductive flame-retardant filler. The improvement in tensile strength is that the vinyl MQ silicone resin coating layer can realize the chemical bond connection between the thermally conductive flame-retardant filler and the silicone rubber matrix, which significantly improves the reinforcement effect. The improvement in elongation is due to the improvement of the clustered cross-linked structure and the MQ silicone resin coating modification on flexibility and elasticity. The improvement of thermal conductivity is due to the improvement of the dispersion uniformity of thermally conductive flame retardant filler by MQ silicone resin coating modification and the improvement of the bonding effect between thermally conductive flame retardant filler and silicone rubber matrix.

[0104] Comparative Example 2

[0105] A low-density thermally conductive potting adhesive. Compared with Example 1, the preparation process of the vinyl MQ silicone resin coated modified thermally conductive flame-retardant filler does not use silicon dioxide for surface modification in advance, and the rest is the same.

[0106] The vinyl MQ silicone resin coated modified thermally conductive flame retardant filler of this comparative example is prepared by the following method:

[0107] Take 100 parts of thermally conductive flame retardant filler (aluminum nitride and aluminum hydroxide in a mass ratio of 5:1) and add them to 100 parts of a vinyl MQ silicone resin (molecular weight 4210 g / mol) toluene solution with a mass concentration of 20%, stir and disperse evenly, and the resulting slurry is spray granulated to obtain a vinyl MQ silicone resin coated modified thermally conductive flame retardant filler.

[0108] The low-density thermally conductive potting adhesive obtained in this comparative example has a hardness (Shore A) of 59 after being cured at 80° C. / 30 min; a tensile strength of 1.12 MPa; an elongation of 86.0%; and a thermal conductivity of 0.99 W / m·K.

[0109] By comparing the results of this comparative example with Example 1, it can be seen that by pre-modifying the surface of the thermally conductive flame retardant filler with silica, the bonding force between the thermally conductive flame retardant filler and the vinyl MQ silicone resin can be improved, the coating modification effect of the vinyl MQ silicone resin can be significantly improved, and ultimately the strength, elongation and thermal conductivity can be further improved.

[0110] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A low-density thermally conductive potting adhesive, characterized in that: It includes component A and component B; The A component includes the following components by weight: 80-100 parts of side vinyl silicone oil and / or terminal vinyl silicone oil; 100-150 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 0.005-0.02 parts of catalyst; The B component includes the following components by weight: 80-100 parts of side vinyl silicone oil and / or end vinyl silicone oil; 100-150 parts of vinyl MQ silicone resin coated modified thermal conductive flame retardant filler; 10-30 parts of end hydrogen silicone oil; 0.05-0.2 parts of inhibitor; 0-0.2 parts of color powder; The vinyl MQ silicone resin coated modified thermally conductive flame retardant filler is prepared by the following method: (1) adding a thermally conductive filler and a flame retardant filler to an ethanol aqueous solution and stirring and dispersing them uniformly, then adding ammonia water to adjust the pH value to 8-10, adding tetraethyl orthosilicate dropwise and stirring to react, and after the reaction is completed, filtering and drying the solid phase, and crushing to obtain a silica-coated modified thermally conductive flame retardant filler; (2) adding the silica-coated modified thermally conductive flame-retardant filler into the vinyl MQ silicone resin solution and stirring to disperse the mixture evenly; spraying and granulating the resulting slurry to obtain the vinyl MQ silicone resin-coated modified thermally conductive flame-retardant filler.

2. A low-density thermally conductive potting adhesive according to claim 1, characterized in that: The viscosity of the side vinyl silicone oil or the terminal side vinyl silicone oil is 100-5000 mPa·s, and the vinyl content is 2%-10%; the terminal hydrogen silicone oil is a terminal hydrogen silicone oil with a hydrogen content of 0.02%-1.5%.

3. The low-density thermally conductive potting adhesive according to claim 1, characterized in that: The catalyst is any one of chloroplatinic acid, chloroplatinic acid-isopropanol, and Custer catalyst; the inhibitor is one or more of 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 2-phenyl-3-butynyl-2-ol, and vinyl ring.

4. The low-density thermally conductive potting adhesive according to claim 2, characterized in that: The hydrogen-terminated silicone oil is a hydrogen-terminated silicone oil having a hydrogen content of 0.05% to 1%.

5. The low-density thermally conductive potting adhesive according to claim 4, characterized in that: The hydrogen-terminated silicone oil is a combination of hydrogen-terminated silicone oil with a hydrogen content of 0.05% to 0.2% and hydrogen-terminated silicone oil with a hydrogen content of 0.4% to 1%.

6. The low-density thermally conductive potting adhesive according to claim 1, characterized in that: The thermal conductive filler in step (1) is one or more of aluminum oxide, aluminum nitride, silicon carbide, zinc oxide, titanium dioxide, and boron nitride; the flame retardant filler is one or more of aluminum hydroxide, magnesium hydroxide, decabromodiphenyl ether, melamine, antimony oxide, and zinc borate.

7. The low-density thermally conductive potting adhesive according to claim 1, characterized in that: The mass ratio of the thermal conductive filler, the flame retardant filler and tetraethyl orthosilicate added in step (1) is 100:15-30:15-30.

8. The low-density thermally conductive potting adhesive according to claim 1, characterized in that: The vinyl MQ silicone resin solution in step (2) refers to a toluene solution, a xylene solution or a cyclopentasiloxane solution of a vinyl MQ silicone resin having a molecular weight of 2000 to 6000 g / mol; the mass ratio of the silica-coated modified thermally conductive flame-retardant filler to the vinyl MQ silicone resin contained in the vinyl MQ silicone resin solution is 100:10 to 30.

9. A method for preparing a low-density thermally conductive potting adhesive according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: 1) Weighing each component by weight, adding side vinyl silicone oil and / or end vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, and catalyst into a vacuum reactor and stirring and mixing to obtain component A; 2) Weigh each component by weight, add side vinyl silicone oil and / or end vinyl silicone oil, vinyl MQ silicone resin coated modified thermal conductive flame retardant filler, end hydrogen silicone oil, and color powder into a vacuum reactor and stir to mix, then add an inhibitor and stir to mix to obtain component B.

10. Application of the low-density thermally conductive potting adhesive according to any one of claims 1 to 8 in potting of new energy vehicle batteries.

Citation Information

Patent Citations

  • Low density heat conduction pouring sealant and preparation method thereof

    CN104861661A

  • Heat-conductive pouring sealant with low specific gravity and low viscosity and preparation method thereof

    CN108130039A

  • Low-density heat-conducting pouring sealant and preparation method thereof

    CN116463104A